2013
DOI: 10.1016/j.jsr.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Visual feedback system to reduce errors while operating roof bolting machines

Abstract: Problem-Operators of roof bolting machines in underground coal mines do so in confined spaces and in very close proximity to the moving equipment. Errors in the operation of these machines can have serious consequences, and the design of the equipment interface has a critical role in reducing the probability of such errors.Methods-An experiment was conducted to explore coding and directional compatibility on actual roof bolting equipment and to determine the feasibility of a visual feedback system to alert ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A visual feedback system has been developed to reduce errors while operating roof bolting machines. 16 Earlier efforts to improve roof bolter safety focused on training 17 and safety interventions that included interlocks. 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A visual feedback system has been developed to reduce errors while operating roof bolting machines. 16 Earlier efforts to improve roof bolter safety focused on training 17 and safety interventions that included interlocks. 18…”
Section: Introductionmentioning
confidence: 99%
“…A visual feedback system has been developed to reduce errors while operating roof bolting machines. 16 Earlier efforts to improve roof bolter safety focused on training 17 and safety interventions that included interlocks. 18 To address this need for improved area lighting and lighting research that addresses modern roof bolter design, NIOSH researchers have developed an LED area luminaire called the Saturn.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques, however, have traditionally focused more on technical aspects of the design and quality of roof bolting machine than on human aspects. Investigations into past accidents showed that human error was a common cause of injuries involving roof bolting operation . In roof bolting operation, the entire work process is closely related to personnel operating activities.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into past accidents showed that human error was a common cause of injuries involving roof bolting operation. 1 In roof bolting operation, the entire work process is closely related to personnel operating activities. Any human error in operation could result in casualties.…”
Section: Introductionmentioning
confidence: 99%